Estimation of broad-sense heritability and variance components for seed yield and agronomic traits in native and exotic safflower (Carthamus tinctorius L.) genotypes (Bangladesh Journal of Botany, 2018)
This study was conducted to estimate broad-sense heritability and variance components for seed yield and some agronomic traits in 100 safflower genotypes. The experiments were carried out in two years at two locations in Iran. The number of seeds per capitol and harvest index had the highest genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV), respectively. The estimated broad-sense heritability for plant height, days to physiological maturity, 1000-seed weight, days to flowering, number of seeds per capitol, number of capitols per plant and seed yield were 86, 76, 74, 70, 68, 44 and 16%, respectively. It was found that plant height, days to physiological maturity, 1000-seed weight, days to flowering and number of seeds per capitol were the least influenced by the environment. The number of capitols per plant and seed yield were most affected by the environment.